2013
DOI: 10.1016/j.amepre.2013.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity in Parks

Abstract: Background Physical inactivity is an important health risk factor that could be addressed at the community level. Purpose To determine whether using a community-based participatory approach with park directors and park advisory boards (PABs) could increase physical activity in local parks. We also tested whether involving PABs would be more effective than working with park directors alone. Design Randomized controlled intervention trial from 10/2007-4/2012 with partial blinding of observers to the conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
68
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(70 citation statements)
references
References 21 publications
1
68
1
Order By: Relevance
“…The study of Cohen demonstrated that moderate physical activity in rats had a preventive and inhibitory effect on the progression of carcinogenesis. 12 Similar observations have been made in female Sprague-Dawley rats in the study of Westerlind et al, in which physical training was shown to delay cancer development and decrease tumor growth. 13 On the other hand, it has been shown by other groups that moderate physical exercise does not affect the development of breast cancer following MNU administration.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…The study of Cohen demonstrated that moderate physical activity in rats had a preventive and inhibitory effect on the progression of carcinogenesis. 12 Similar observations have been made in female Sprague-Dawley rats in the study of Westerlind et al, in which physical training was shown to delay cancer development and decrease tumor growth. 13 On the other hand, it has been shown by other groups that moderate physical exercise does not affect the development of breast cancer following MNU administration.…”
Section: Introductionsupporting
confidence: 69%
“…15,16 Studies by Cohen and S'aez et al have shown that excessively high or low levels of intensity of physical activity are the leading factors influencing breast cancer progression. 12,17 Low intensity and short duration of physical activity were observed to enhance the rate of occurrence of mammary tumors, while increasing intensity and duration of exercise resulted in a protective effect against mammary cancer development. 9 However, the study of Whittal-Strange et al has demonstrated that already developed tumors increase in weight following excessively intense exercise.…”
Section: Introductionmentioning
confidence: 99%
“…We pooled data collected from five primary studies conducted by us (Cohen et al, 2013; Cohen et al, 2012a; Cohen et al, 2010; Cohen et al, 2012b; Cohen et al, 2007) between 2003 and 2014 (one study is still ongoing). The five previous studies included 37% (n=83) of the neighborhood park and recreation center system in the City of Los Angeles, covering a wide variety of neighborhoods with mild oversampling in low-income areas.…”
Section: Methodsmentioning
confidence: 99%
“…Parks’ size is associated with park use (Cohen et al, 2010), and often varies within cities, with smaller parks in the dense urban cores and larger ones in the periphery, based on land cost and availability at the time the areas were developed (Dahmann et al, 2010). Prior studies have also indicated that the use of parks is highly dependent on programming within the park, e.g., group exercises, classes, and organized sports events (Cohen et al, 2013; Cohen et al, 2012a). Moreover, the use of parks may be reduced where the community considers the spaces unsafe, poorly maintained, or poorly equipped (Babey et al, 2005; Babey et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…[41, 42] Members of lower SES tend to have less access to opportunities to engage in organized sports and are less likely to have the means to pursue other recreational physical activities. However, when resources are provided, physical activity has been observed to increase.…”
Section: Introductionmentioning
confidence: 99%